High-Performance Thin Layer Chromatography Method for Simultaneous Estimation of Water-Soluble Vitamins: Analytical Method Development, Validation and Applications. Issue 5 (3rd September 2022) - Kher, Mukesh N.; Dholakia, Sandip P.; Shah, Grisha G.; Sureja, Dipen K.; Bhatt, Vaibhav D.; Sheth, Devang B.
Abstract: Vitamins are pivotal ingredients in dietary supplements and nutraceutical products. Since many vitamins are unstable and rapidly degraded, it's crucial to keep track of their loss throughout processing and storage. Monitoring hydrophilic vitamins may be more crucial than monitoring those lipophilic vitamins because the body does not maintain them as well. There seems to be a need for an all-encompassing method to estimate hydrophilic vitamins. In this study, we have developed a high-performance thin layer chromatography method for estimation of four water-soluble vitamins simultaneously using HPTLC silica-gel 60GF254 plates and ethyl acetate: methanol: hydrochloric acid (0.1N) (8.5:1:0.5 v/v/v) as a mobile phase, which was successfully validated as per the ICH guideline. All the validation parameters were within the acceptable range established by the ICH guideline. The method is precise, reproducible, easy, reliable, and applicable for the estimation of water-soluble vitamins in marketed products. To best of our knowledge, it is simpler, less time-consuming, and more economical than other approaches that have been published for the same purposes GRAPHICAL ABSTRACT: UF0001